Non-canonical signalling mediates changes in fungal cell wall PAMPs that drive immune evasion - Pradhan, Arnab (Nat Commun, 2019)
To colonise their host, pathogens must counter local environmental and immunological challenges. Here, we reveal that the fungal pathogen Candida albicans exploits diverse host-associated signals to promote immune evasion by masking of a major pathogen-associated molecular pattern (PAMP), β-glucan. Certain nutrients, stresses and antifungal drugs trigger β-glucan masking, whereas other inputs, such as nitrogen sources and quorum sensing molecules, exert limited effects on this PAMP. In particular, iron limitation triggers substantial changes in the cell wall that reduce β-glucan exposure. This correlates with reduced phagocytosis by macrophages and attenuated cytokine responses by peripheral blood mononuclear cells. Iron limitation-induced β-glucan masking depends on parallel signalling via the iron transceptor Ftr1 and the iron-responsive transcription factor Sef1, and the protein kinase A pathway. Our data reveal that C. albicans exploits a diverse range of specific host signals to trigger protective anticipatory responses against impending phagocytic attack and promote host colonisation.